Implementation Of Basic Literacy Activities On The Reading Interest Of Grade 2 Students MI Salafiyatul Huda 1 Cirebon City - Kubah, Kubah; Maufur, Syibli; Laily, Idah Faridah (UIN Siber Syekh Nurjati Cirebon, 2024)
In the implementation of basic literacy activities for the reading interest of 2nd grade students of Mi Salafiyatul Huda 1 Cirebon City has been implemented but has not been maximized in carrying it out. The type of research used in this study uses a qualitative approach, the method used in this study is a description method with a descriptive design. Data collection techniques use observation, interviews, questionnaires and documentation. The subjects in the study were all 2nd grade students at MI Salafiyatul Huda 1 Cirebon City which amounted to 27 students. The data is processed using data reduction, data display and ferification. From the results of the study, it can be seen that. 1. the implementation of basic literacy activities at MI Salafiyatul Huda 1 Cirebon City, namely, First, managing several reading resources in books such as Indonesian, and so on, namely to students to increase their interest in reading so that the basic literacy activities carried out can run well, Second, there is tutoring from teachers to students so that they can read vocabulary fluently through basic literacy activities, and lastly, there is cooperation between both parents and teachers at school to get students used to learning at home. 2. Obstacles and Solutions to the implementation of basic literacy activities on the reading interest of grade 2 students of Mi Salafiyatul Huda 1 Cirebon City, namely the first one that has is that students are lazy to read, feel bored quickly reading with this then make teachers inconsistent in supervising students in basic literacy activities, secondly implementing basic literacy activities by reading non-lesson books in literacy activities. 3. This can be anticipated at least by making a habit of compulsory reading for students for 15 minutes before class hours start every day so that students are not easily bored and lazy to read books.Keywords: Basic Literacy Activities, Reading Interest, Grade 2 Student